Comparison of Interdisciplinary Connections between Mathematic and other Subjects through Student-centred Approaches - Andreja Drobnič Vidic (REDIMAT, 2023)
In some European countries inquiry-based learning (IBL) has become popular in primary and secondary mathematics education, especially for science-connected content. On the other hand, problem-based learning (PBL) and project-based learning (PjBL) have a longer history in mathematics, science, technology, engineering (STEM) and in some other fields in higher education. After presenting the theoretical similarities and differences among these three interdisciplinary student-centred approaches, we review the use of them in mathematics education. We analyse a selection of n=112 high quality research articles about the use of IBL, PBL or PjBL in mathematics, and its interdisciplinary connection with other subjects, level of education, type of research method, research design and participants for each study. Based on these characteristics, we identify the differences between the approaches in mathematics education. Finally, detailed examination of a subsample of experimental studies, where effect size is or can be measured, describes differences in interdisciplinary connections between the target approaches and indicate what kind of studies are still missing in mathematics education.